Acetylcholinesterase inhibitory activity and molecular docking study of steroidal alkaloids from Holarrhena pubescens barks - Cheenpracha S. (2017)
© 2016 Elsevier Inc. All rights reserved. An alkaloidal extract of the bark of Holarrhena pubescens showed several inhibition zones of acetylcholinesterase (AChE) inhibitor, using a bioautographic assay. Activity-guided fractionation afforded three new steroidal alkaloids, mokluangins A-C (1-3), together with three known compounds, antidysentericine (4), holaphyllamine (5), methylholaphyllamine (6). All structures were elucidated by analysis of NMR and MS spectroscopic data. Compound 2 showed moderate antibacterial activity against Bacillus subtilis and Escherichia coli with the MIC value of 16 μg/mL, while compound 3 exhibited moderate selective activity against E. coli with the MIC value of 16 μg/mL. In addition, compounds 1-4 also showed strong AChE inhibiting activity with IC 50 values ranging from 1.44 to 23.22 μM. Molecular docking calculations were also performed and the results demonstrated that all compounds can bind at the aromatic gorge of AChE with estimated binding free energies correlated well with the in vitro inhibitory profiles. Hydrophobic and hydrogen bonding interactions contribute mainly to the binding of the alkaloids where the substituents at C-3 serving as key functional groups for the AChE inhibition. Our results will allow the development of new AChE-inhibitors based on steroidal alkaloid skeleton bearing the cyclic amide moiety.